Dick Watkins: Reshaping Art and Life - Eagle, Mary (ANU Press, 2024)
Dick Watkins belongs to the generation of artists whose careers were launched at the high-flying end of American-based Abstraction. Almost immediately he faced up to the abrupt end of the Modern era. Culture was no longer to be framed by 'progress'. In 1970, taking stock of the situation, he announced that he was a copyist, there being no such thing as a new creation in art, shaped as it was by visual languages. Nor did he intend to limit his curiosity about the relation of art to life by restricting himself to a ‘personal’ style. There followed a long and passionately adventurous exploration into many subjects and styles, during which Watkins was often the first to signal changes taking place in Western culture. The result is that for half a century he has been a major, if controversial figure in Australian art.